FgVps9, a Rab5 GEF, Is Critical for DON Biosynthesis and Pathogenicity in Fusarium graminearum - Yang, Chengdong; Li, Jingjing; Chen, Xin; Zhang, Xingzhi; Liao, Danhua; Yun, Yingzi; Zheng, Wenhui; Abubakar, Yakubu Saddeeq; Li, Guangpu; Wang, Zonghua; Zhou, Jie (Frontiers in Microbiology, 2020)
Rab GTPases play an important role in vesicle-mediated membrane trafficking in eukaryotes. Previous studies have demonstrated that deletion of RAB5/VPS21 reduces endocytosis and virulence of fungal phytopathogens in their host plants. However, Rab5 GTPase cycle regulators have not been characterized in Fusarium graminearum, the causal agent of Fusarium head blight (FHB) or head scab disease in cereal crops. In this study, we have identified and characterized a Rab5 guanine nucleotide exchange factor (GEF), the Vps9 homolog FgVps9, in F. graminearum. Yeast two hybrid (Y2H) assays have shown that FgVps9 specifically interacts with the GDP-bound (inactive) forms of FgRab51 and FgRab52, the Rab5 isoforms in F. graminearum. Deletion of FgVPS9 shows impaired fungal growth and conidiation. Pathogenicity assays indicate that deletion of FgVPS9 can significantly decrease the virulence of F. graminearum in wheat. Cytological analyses have indicated that FgVps9 co-localizes with FgRab51 and FgRab52 on early endosomes and regulates endocytosis and autophagy processes. Gene expression and cytological examination have shown that FgVps9 and FgRab51 or FgRab52 function in concert to control DON biosynthesis by regulating the expression of trichothecene biosynthesis-related genes and toxisome biogenesis. Taken together, FgVps9 functions as a GEF for FgRab51 and FgRab52 to regulate endocytosis, which as a basic cellular function has significant impact on the vegetative growth, asexual development, autophagy, DON production and plant infection in F. graminearum.